Effects of inoculation with Bradyrhizobium on nodulation pattern, nodule senescence and size distribution in mungbean (Bangladesh Journal of Agricultural Research, 2007)
An experiment was carried out with five mungbean varieties with or without Bradyrhizobium at Bangladesh Agricultural University Farm during kharif-1 2001 and kharif-1 2002 seasons to find out the time of nodule initiation, nodulation pattern and their size distribution. Five mungbean varieties viz., BARI Mung-2, BARI Mung-4, BARI Mung-5, BINA Mung-2 and Barisal local, and rhizobial inoculum (Bradyrhizobium strain BAUR-604) were used in this experiment. The experiment was designed in RCBD having four replications in each treatment. Each variety was tested with/without inoculation. For recording nodule size, nodules were collected from roots and were grouped on the basis of their size in diameters. The results suggested that nodule initiation in the roots of mungbean varieties started at 9 days of sowing seeds (DAS), reached the peak at 42 DAS and thereafter started reducing in numbers until 70 DAS due to spontaneous degeneration. BARI Mung-2 always produced larger size nodules at all sampling dates in both the years. Smaller size (